Effectiveness of Wastewater Treatment Plant (WWTP) in Semanggi, Surakarta City - Putri Rumaira, Ainaya; Astuti, Dwi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The increase in pollution load from domestic activities demands the existence of an effective wastewater treatment system to protect environmental quality and public health. Therefore, this study was conducted to evaluate the effectiveness of the Semanggi Wastewater Treatment Plant (WWTP), Surakarta City, in improving the quality of domestic wastewater. Wastewater samples were taken at the influent and effluent points, then analyzed based on physicochemical and biological parameters, including pH, BOD, COD, TSS, ammonia, total detergent, oil and grease, residual chlorine, and fecal coliform. The results showed that the influent wastewater exceeded quality standards in several parameters, indicating a high load of organic and biological pollutants. After the treatment process, all parameters met the quality standards for domestic wastewater according to Regulation No. 11/2025. The efficiency of BOD, COD, TSS, and fecal coliform removal reached over 80%, categorizing it as very effective, while ammonia and residual chlorine were also effectively reduced. Oil and grease experienced moderate reduction, and total detergent showed low removal efficiency, but the effluent concentration remained within safe limits. Overall, the results confirm that the Semanggi Wastewater Treatment Plant operates well in reducing domestic wastewater pollutants and plays an important role in environmental protection efforts and improving public health.